2014
DOI: 10.3390/catal4030299
|View full text |Cite
|
Sign up to set email alerts
|

New Trends in Gold Catalysts

Abstract: Gold is an element that has fascinated mankind for millennia. The catalytic properties of gold have been a source of debate, due to its complete chemical inertness when in a bulk form, while it can oxidize CO at temperatures as low as ~200 K when in a nanocrystalline state, as discovered by Haruta in the late 1980s [1]. Since then, extensive activity in both applied and fundamental research on gold has been initiated. The importance of the catalysis by gold represents one of the fasted growing fields in scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Nevertheless, carbon supported Au is relatively rarely studied. One of the reasons for this is the difficulty of synthesizing highly dispersed (<3 nm) gold nanoparticles with a narrow particle size distribution [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, carbon supported Au is relatively rarely studied. One of the reasons for this is the difficulty of synthesizing highly dispersed (<3 nm) gold nanoparticles with a narrow particle size distribution [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that one of the most chemically inert metals, gold, is very active as a catalyst when it is dispersed in nanometric sizes less than 5 nm and when it is prepared in an appropriate manner. This characteristic has been observed even for gold clusters deposited on an inert support, in solution, or in gaseous phase. In general terms, the gold catalytic activity has been largely attributed to the high reactivity at the particles zones such as edges and corners, where the gold atoms have low coordination numbers. , In fact, it has been found that (a) the fraction of low-coordinated Au atoms, and not the particles surface area, scales approximately with the catalytic activity, (b) usually the Au catalytic activity is strongly dependent on the particle size and shape, increasing with the decrease in size, ,, (c) very small neutral Au n clusters, with n ranges from 1 to 11, have outstanding catalytic activity ,,, (d) small Au nanoparticles are sufficiently reactive to catalyze reactions at or even to very low temperatures, , and (e) the catalytic activity of gold is, in important cases, very selective. …”
Section: Introductionmentioning
confidence: 99%
“…In view of presented results, the 0.1% Au/SiO 2 catalyst seems to have prospects for wide applications for alcohol oxidation, and notably, SiO 2 appears to be a promising support material for nanogold particles. This is an intriguing finding taking into account the recent trends in the investigation for an optimal material for nano-Au support, which is one use of reducible metal oxides, usually Fe 3 O 4 , ZnO, CeO 2 , and TiO 2 [28]. In fact, the interactions between the active phase and active support (e.g., Au–TiO 2 , Au–Fe 3 O 4 ) via the formation of oxygen vacancies in reducible metal oxides are recognized as being one of the most effective ways to enhance the catalytic properties [29].…”
Section: Resultsmentioning
confidence: 99%